Amsterdam Human Capital - Musterd, Sako; Salet, Willem (Amsterdam University Press, 2003)
The familiar shape of western cities is changing dramatically. For long times the urban core was taken for granted as the focal point for international contacts and day-to-day activities in the region. Currently, the urban scope is transforming into multi centred forms at metropolitan scale. The transition is not just a matter of spatial form, it is reflecting social, economic and cultural processes. The question is what new identities may develop in such changing historical conditions of space and place. The book is a first attempt to analyse the process of urban transformation in an integral way. The focus is on the region of Amsterdam. All contributions are written by senior researchers of the Amsterdam studycentre for the Metropolitan Environment (AME). AME is the interdisciplinary urban research institute of the Universiteit van Amsterdam. As the urban research institute at the Universiteit van Amsterdam, the Amsterdam studycentre for the Metropolitan Environment (AME) analyses the economic, social and cultural aspects of this spatial transformation, usually in international comparative research. All contributions to this book are written by senior researchers of AME in an attempt to analyse in an integral way the present and future dilemmas out of the historical growth paths of this dynamic city.